Randomized, Standard Controlled Study Evaluating the Efficacy and Safety of Habb-e-Waja‘al-Mafāṣil in Managing Cervical Spondylosis - safia husain; rather, shameem ahmad; bhat, shabir ahmad (International Journal of Medical Research and Review, 2023)
Background and Objectives Cervical Spondylosis is a degenerative disease of intervertebral discs and adjacent vertebral bodies of the cervical region due to wear and tear changes. Neck pain, with radiculopathy, and stiffness comprises the prime features of cervical spondylosis demanding the immediate attention and respite. Despite the advancement in pharmacological, nonpharmacological and surgical interventions, the management remains unsatisfactory due to high cost, adverse effects and unusual eventualities. Hence a clinical trial was done to evaluate the efficacy of herbal formulation, Habb-e-Waja‘al-Mafāṣil (HWM), in managing cervical spondylosis (Waja‘al-‘Unuq). Methods The study is an open-labeled, randomized and standard controlled trial. Sixty diagnosed patients of age group 20 to 70 years were randomly allocated, using a computer generated chart, in test group (n=30) receiving HWM (3gm), and the control group (n=30) receiving ibuprofen 1200mg/day, orally in divided doses. The severity score of clinical symptoms and signs; pain, stiffness, swelling, restriction of movement and radiological findings were analyzed at baseline and at 30 days. Results Both HWM and ibuprofen significantly reduced the severity score of pain, stiffness, swelling, and restriction of movement (p=<0.001) associated with cervical spondylosis after completion of treatment protocol. However, no change was observed in radiological findings in either group (p=1). Comparison to control group no significant result was noticed in test group statistically (p=>0.05), except for “restriction of movement” (p=<0.05). Conclusion The herbal formulation, HWM, is equally effective to conventional treatment in managing cervical spondylosis. Therefore, HWM can be prescribed as safe and cost effective alternative treatment for cervical spondylosis.